KIMURA DISEASE: A RARE ENTITY - Nur Raihann Kamal; Nik Ameera Syafiqa Mohd Azhar; Wahinuddin Sulaiman (Asian Journal of Medicine & Health Sciences, 2020)
Kimura disease (KD) is a chronic inflammatory condition with a benign course, commonly affecting the head and neck region. The underlying aetiology is still uncertain. The prevalence of this condition is unknown. It has been reported sporadically especially in Asian region predominantly in young males. We report a 48-year-old Malay man who presented with progressive swelling over the right cheek which responded well to corticosteroid and leflunomide.